Prophylaxis of Cytomegalovirus in Renal Transplant Recipients - Allan S MacDonald; David L Nicol; Philip Belitsky; Spencer Lee (Canadian Journal of Infectious Diseases)
The incidence and outcome of cytomegalovirus (CMV) infection and disease is compared in renal transplant recipients in relation lo the use of prophylaxis wiU1 high titre anti-CMV immunoglobulin. Seventy-three CMV-negative recipients (R-) who received kidneys from CMV-posilive donors (D+) were given prophylactic CMV hyperimmune globulin inlravenously al three-week intervals lo six monilis. They also received Lhree months of oral low dose acyclovir as did the remaining 288 patients who did nol receive hyperimmune globulin. There was a low incidence of CMV disease which did not differ between groups (D+R-, 10%: D+R+, 5 .5%, D- R+, 7%: D- R-, 0.8%). The major risk factor was the use of OKT3 to treat rejection. CMV disease was seen in 22% of this group (11 of 50) . compared with only 2% (seven of 311) of those not requiring OKT3. There was only one CMV-related death. but palients with CMV disease had a reduced graft survival rate (62% versus 90%). CMV hyperimmune globulin added lo acyclovir appears to reduce the incidence of CMV disease in high risk renal recipients (D+R-) in the lower risk groups.